To solve 2w^2 - 11w = -12 by factoring, we first rearrange the equation to set it equal to zero:
2w^2 - 11w + 12 = 0
Next, we need to factor the quadratic equation. The factors are:
(2w - 3)(w - 4) = 0
Setting each factor to zero gives us the solutions:
2w - 3 = 0 -> 2w = 3 -> w = 3/2
w - 4 = 0 -> w = 4
Therefore, the solutions to the equation are w = 3/2 or w = 4.
So, the correct choice is: w = 3/2 or 4.
Solve by factoring.
2w^2- 11w=-12
(1 point)
w= 3/2 or 4
w= 1 or 12
w= 1 or 7
w= 2.5 or 6
1 answer